Polymer, positive electrode material and preparation method thereof, raw material composition of positive electrode material, electrode sheet and battery
Patent Information
- Application Number
- CN202610913036.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-06-24
AI Technical Summary
[0007]本发明要解决的技术问题是为了克服现有技术中的碳源存在一些不足导致所得正极材料制得的电池电化学性能较差的缺陷,提供一种聚合物、正极材料及其制备方法、正极材料的原料组合物、极片和电池
采用本申请的聚合物作为碳源制得的正极材料具有较低的粉末电阻率、较高的电导率和较佳的压实密度;由该正极材料制得的电池具有优异的电化学性能。
Smart Images

Figure CN122427334B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a polymer, a cathode material and its preparation method, a raw material composition for the cathode material, an electrode sheet, and a battery. Background Technology
[0002] In the field of new energy storage, especially in the research and development of secondary batteries such as lithium-ion batteries and lithium-sulfur batteries, the electrochemical performance of cathode materials is one of the core factors determining the battery's energy density, cycle stability, and rate performance. Because most cathode active materials (such as lithium iron phosphate, lithium nickel manganese oxide, and elemental sulfur) suffer from poor electronic conductivity, low ion migration rates, or are susceptible to electrolyte corrosion and side reactions during charging and discharging, they typically require the introduction of carbon sources for modification. This is achieved by forming carbon coating layers and constructing porous carbon carriers, thereby improving the electron transport efficiency of the cathode material, mitigating structural damage, and ultimately optimizing the battery's overall performance.
[0003] Polymers, as carbon sources for cathode materials, have become a research hotspot in recent years due to their advantages such as wide availability, controllable cost, tunable structure, and ease of large-scale production, resulting in a relatively rich array of applications. In terms of polymer types, these include synthetic polymers such as polyimide and polyaniline, as well as natural polymers such as chitosan and cellulose, and even recyclable polymers such as waste plastics. These polymers, after pyrolysis and carbonization, can be transformed into carbon materials with certain conductivity and porous structures. They can serve as conductive additives to improve electron transport in the cathode, and as coating layers to isolate the electrolyte from the cathode active material, reducing side reactions. Among these, synthetic polymers can have their functional group composition controlled through molecular design, achieving heteroatom doping (such as N and O doping) of the carbon layer, further enhancing the catalytic activity and ion adsorption capacity of carbon materials. Natural polymers and waste plastics as carbon sources align with the concept of green and sustainable development, achieving high-value utilization of resources. In particular, the application of waste plastics as carbon sources can simultaneously meet the dual needs of waste treatment and energy storage, demonstrating significant environmental benefits and application potential. In terms of application scenarios, polymer-derived carbon sources have been widely used in various systems such as lithium iron phosphate, lithium nickel manganese oxide, and lithium-sulfur battery cathodes. Through processes such as in-situ polymerization-carbonization and carbothermal reduction, the electrochemical performance of cathode materials has been improved to a certain extent.
[0004] Despite the numerous advantages of polymers as cathode carbon sources, their application in current technologies still faces many insurmountable shortcomings, severely restricting further optimization of cathode material performance and industrial application. Poor carbon coating uniformity is the most prominent problem. Most polymers tend to agglomerate in solution or have insufficient interfacial bonding with the cathode active material, resulting in uneven carbon layer thickness and incomplete coverage after carbonization. Some areas exhibit missing carbon layers, failing to effectively isolate the electrolyte, while excessively thick carbon layers in other areas hinder lithium-ion transport, limiting the improvement in cycle stability and rate performance of the cathode material. This problem is particularly evident in the carbothermic reduction preparation process of lithium iron phosphate cathodes, and is further accompanied by derivative issues such as inconsistent particle growth and large fluctuations in electrical performance.
[0005] In addition, polymer carbon sources have other inherent defects: First, the carbon residue rate is low. After high-temperature carbonization, most polymers lose a large amount of carbon in gaseous form, resulting in low carbon source utilization. Excessive polymer needs to be added to achieve the expected carbon coating effect, which not only increases production costs but may also lead to a decrease in the compaction density of the cathode material due to excessive carbon residue, affecting the energy density of the battery. Second, the compatibility between polymers and cathode active materials is difficult to control. The functional groups of some polymers lack effective interaction with the surface groups of cathode active materials, resulting in weak bonding between the carbon layer and the active material. During long-term charge-discharge cycles, peeling and shedding can easily occur, leading to the collapse of the cathode structure and rapid degradation of battery performance.
[0006] In summary, although polymers have shown promising application prospects as carbon sources for cathode materials in existing technologies, their defects in carbon coating uniformity, carbon source utilization, and compatibility limit their widespread application in high-performance cathode materials. Therefore, developing polymer carbon source modification technologies that can solve the above defects has become an important research direction in the field of new energy materials. Summary of the Invention
[0007] The technical problem this invention aims to solve is to overcome the shortcomings of existing carbon sources, which lead to poor electrochemical performance of batteries made from the resulting cathode materials. This invention provides a polymer, a cathode material, a method for preparing the same, a raw material composition for the cathode material, an electrode sheet, and a battery. The cathode material prepared using the polymer of this application as a carbon source exhibits low powder resistivity, high conductivity, and good compaction density; the battery made from this cathode material demonstrates excellent electrochemical performance.
[0008] The present invention solves the above-mentioned technical problems through the following technical solution: The present invention provides a method for preparing a polymer, comprising the following steps: in the presence of an initiator, carrying out a polymerization reaction of a base liquid, solution A and solution B; The underlying solution comprises an unsaturated polyether monomer solution; solution A comprises a mixed solution of unsaturated aromatic monomers, unsaturated nitrile monomers, and acrylic compounds; solution B comprises a mixed solution of chain transfer agents and reducing agents. The unsaturated polyether monomer is an unsaturated polyoxyethylene ether; the unsaturated aromatic monomer is an unsaturated vinyl aromatic monomer; the unsaturated nitrile monomer is one or more of acrylonitrile, methacrylonitrile, and vinyl acetonitrile; the acrylic compound is one or more of acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, methyl methacrylate, butyl methacrylate, and hydroxyethyl methacrylate. The molar ratio of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer, and acrylic compound is 1.0:(0.2-7.0):(0.2-7.0):(0.2-8.0). The polymerization reaction is carried out at a temperature of 30-50℃ and for a time of 60-120 minutes.
[0009] In this invention, the unsaturated polyether monomer refers to a compound whose molecule contains polymerizable carbon-carbon unsaturated double bonds and contains polyoxyethylene ether or polyoxypropylene ether. The unsaturated polyether monomer is preferably an unsaturated alkenyl polyoxyethylene ether, such as one or more of methyl allyl alcohol polyoxyethylene ether, isopentenyl alcohol polyoxyethylene ether, and allyl polyoxyethylene ether.
[0010] The structural formula of the methyl allyl alcohol polyoxyethylene ether is as follows:
[0011] In the formula, n1 = 5-150, preferably 30-80, for example 52 or 54.
[0012] The structural formula of the isopentenyl alcohol polyoxyethylene ether is as follows:
[0013] In the formula, n2 = 5-150, preferably 30-80, for example 52.
[0014] In this invention, the unsaturated aromatic monomer refers to a compound containing an aromatic ring and polymerizable unsaturated bonds in its molecule. The unsaturated aromatic monomer is preferably one or more of styrene, α-methylstyrene, vinyltoluene, and naphthylene, for example, styrene and / or vinyltoluene.
[0015] In this invention, the unsaturated nitrile monomer refers to a compound containing a nitrile group and a polymerizable unsaturated double bond in its molecule. The unsaturated nitrile monomer is preferably acrylonitrile and / or methacrylonitrile.
[0016] In this invention, the acrylic compound refers to a compound containing a carbon-carbon double bond and a carboxyl group, a carboxylic acid ester group, or an amide group. Preferably, the acrylic compound is acrylic acid, methyl methacrylate, or hydroxypropyl acrylate.
[0017] In a preferred embodiment, the raw material composition of the polymer includes unsaturated alkenyl polyoxyethylene ether, unsaturated vinyl aromatic monomer, unsaturated nitrile monomer and acrylic acid.
[0018] In a preferred embodiment, the raw material composition of the polymer includes unsaturated alkenyl polyoxyethylene ether, unsaturated vinyl aromatic monomer, unsaturated nitrile monomer and methacrylic acid.
[0019] In a preferred embodiment, the raw material composition of the polymer includes unsaturated alkenyl polyoxyethylene ether, unsaturated vinyl aromatic monomer, unsaturated nitrile monomer and methyl methacrylate.
[0020] In a preferred embodiment, the raw material composition of the polymer includes unsaturated alkenyl polyoxyethylene ether, unsaturated vinyl aromatic monomer, unsaturated nitrile monomer and hydroxypropyl acrylate.
[0021] In a preferred embodiment, the raw material composition of the polymer includes methyl allyl alcohol polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid. The molar ratio of methyl allyl alcohol polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid is preferably 1.0:2.0:1.5:2.5.
[0022] In a preferred embodiment, the raw material composition of the polymer includes methyl allyl alcohol polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid. The molar ratio of methyl allyl alcohol polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid is preferably 1.0:1.0:2.5:2.5.
[0023] In a preferred embodiment, the raw material composition of the polymer includes methyl allyl alcohol polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid. The molar ratio of methyl allyl alcohol polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid is preferably 1.0:1.0:1.0:3.0.
[0024] In a preferred embodiment, the raw material composition of the polymer includes isopentenyl polyoxyethylene ether, styrene, acrylonitrile, and methacrylic acid. The molar ratio of isopentenyl polyoxyethylene ether, styrene, acrylonitrile, and methacrylic acid is preferably 1.0:2.5:1.5:2.0.
[0025] In a preferred embodiment, the raw material composition of the polymer includes isopentenyl polyoxyethylene ether, styrene, acrylonitrile, and methyl methacrylate. The molar ratio of isopentenyl polyoxyethylene ether, styrene, acrylonitrile, and methyl methacrylate is preferably 1.0:1.0:2.5:2.5.
[0026] In a preferred embodiment, the raw material composition of the polymer includes isopentenyl polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid. The molar ratio of isopentenyl polyoxyethylene ether, styrene, acrylonitrile, and acrylic acid is preferably 1.0:2.0:1.5:2.5.
[0027] In a preferred embodiment, the raw material composition of the polymer includes methyl allyl alcohol polyoxyethylene ether, vinyl toluene, acrylonitrile, and acrylic acid. The molar ratio of methyl allyl alcohol polyoxyethylene ether, vinyl toluene, acrylonitrile, and acrylic acid is preferably 1.0:2.0:1.5:2.5.
[0028] In a preferred embodiment, the raw material composition of the polymer includes methyl allyl alcohol polyoxyethylene ether, styrene, methacrylonitrile, and acrylic acid. The molar ratio of methyl allyl alcohol polyoxyethylene ether, styrene, methacrylonitrile, and acrylic acid is preferably 1.0:2.0:1.5:2.5.
[0029] In a preferred embodiment, the raw material composition of the polymer includes methyl allyl alcohol polyoxyethylene ether, styrene, methacrylonitrile, and hydroxyethyl acrylate. The molar ratio of methyl allyl alcohol polyoxyethylene ether, styrene, methacrylonitrile, and hydroxyethyl acrylate is preferably 1.0:2.0:1.5:2.5.
[0030] In a preferred embodiment, the raw material composition of the polymer includes allyl polyoxyethylene ether, styrene, methacrylonitrile, and acrylic acid. The allyl polyoxyethylene ether, styrene, methacrylonitrile, and acrylic acid are preferably in a ratio of 1.0:2.0:1.5:2.5.
[0031] In this invention, the molar ratio of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer and acrylic compound is preferably 1.0:(0.8-5):(0.8-3):(2-5), for example 1.0:2.0:1.5:2.5, 1.0:3.0:1.0:3.0, 1.0:2.5:1.5:2.0 or 1.0:1.0:2.5:2.5.
[0032] In this invention, the initiator can be of conventional types in the art, preferably one or more of hydrogen peroxide, ammonium persulfate, and cumene hydrogen peroxide, such as hydrogen peroxide, ammonium persulfate, or cumene hydrogen peroxide. The amount of the initiator is preferably 0.2%-2% of the total mass of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer, and acrylic compound, more preferably 0.18%-1%, for example 0.19%, 0.20%, 0.25%, or 0.30%.
[0033] In this invention, the reducing agent can be of conventional types in the art, preferably vitamin C and / or vitamin E. The molar ratio of the initiator to the reducing agent is preferably (2-7):1, more preferably (4-6):1, for example 4.5:1, 5.0:1, 5.3:1 or 5.8:1.
[0034] In this invention, the chain transfer agent can be of conventional types in the art, preferably one or more selected from mercaptoethanol, mercaptoacetic acid, mercaptopropionic acid, n-dodecyl mercaptan, tert-dodecyl mercaptan, and octyl mercaptan, such as mercaptoethanol, tert-dodecyl mercaptan, mercaptoacetic acid, or n-dodecyl mercaptan. The amount of the chain transfer agent is preferably 0.1%-3% of the total mass of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer, and acrylic compound, more preferably 0.4%-1%, for example 0.5%, 0.6%, 0.7%, or 0.8%.
[0035] In this invention, the solvents in the base liquid, solution A, and solution B can each be conventional in the art, preferably ethyl acetate.
[0036] In this invention, the polymerization reaction time is, for example, 60, 80, 90 or 100 min.
[0037] In this invention, the polymerization reaction preferably includes a purification step conventional in the art. The purification operation can be conventional in the art, such as vacuuming. During purification, the vacuum level of the system is preferably -100 to -90 kPa, for example -95, -97, -98, or -100 kPa. The solvent removal time is preferably 30-90 min, for example 30, 50, 70, or 90 min.
[0038] In this invention, the solvent in the base solution can be conventional in the art, such as ethyl acetate. The mass concentration of the base solution is preferably 40%-60%, for example, 40%, 50%, 55%, or 60%. The preparation method of the base solution preferably includes the following steps: mixing and stirring the unsaturated polyether monomer and the solvent. The mixing temperature is preferably 40-50°C, for example, 45°C. The stirring speed is preferably 400-600 r / min, for example, 500 r / min.
[0039] In this invention, the solvent in solution A can be conventional in the art, such as ethyl acetate. The mass concentration of solution A is preferably 40%-60%, for example, 40%, 50%, 55% or 60%.
[0040] In this invention, the solvent in solution B can be of a type conventional in the art, such as ethyl acetate. The mass concentration of solution B is preferably 1%-5%, for example 1.7%, 1.8%, 2% or 2.5%.
[0041] In this invention, the total amount of solvent in solution A and solution B is preferably 0.2 to 4.0 times the total mass of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer and acrylic compound, more preferably 0.8 to 2.5 times, for example 1.0 times, 1.2 times, 1.5 times or 2 times.
[0042] In this invention, solutions A and B are preferably added dropwise. The dropwise addition time for solution A is preferably 40-80 minutes, for example, 70, 55, or 60 minutes. The dropwise addition time for solution B is preferably 60-90 minutes, for example, 70, 75, or 85 minutes.
[0043] In this invention, the volume ratio of solution A to solution B is preferably (3-5):1, for example 4:1.
[0044] This invention provides a polymer prepared using the polymer preparation method described above.
[0045] In this invention, the weight-average molecular weight of the polymer can be 10,000-80,000, preferably 20,000-50,000, for example 36118, 42282, 38100 or 35397.
[0046] In this invention, the PDI of the polymer can be 1.5-2.5, preferably 1.7-2.1, such as 2.039820, 1.799366, 1.706434 or 1.850811.
[0047] The present invention provides a raw material composition for a cathode material, which includes a carbon source, said carbon source comprising the polymer as described above.
[0048] In this invention, the percentage of the carbon source in the total mass of the raw material composition of the cathode material (excluding the solvent) can be 2%-20%, preferably 4%-15%, for example 8.9%, 8.2%, 9.5%, 5.3%, 5.0%, 5.8% or 12%.
[0049] In this invention, the polymer accounts for 20%-80% of the mass percentage of the carbon source, preferably 40%-60%, for example 50%, 45.5%, 53.8%, 55.6%, 52.9% or 60%.
[0050] In this invention, the carbon source may preferably include other carbon sources, more preferably one or more of sucrose, glucose, polyethylene glycol, starch, citric acid, and asphalt, such as polyethylene glycol and / or glucose. The polyethylene glycol is preferably PEG1500, PEG6000, or PEG-200.
[0051] In a preferred embodiment, the carbon source includes glucose and the polymer, and the mass ratio of glucose to the polymer can be (0.2-2):1, preferably (0.5-1.5):1, for example 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5 or 4:6.
[0052] In a preferred embodiment, the carbon source includes glucose and polyethylene glycol, and the mass ratio of glucose to polyethylene glycol can be (0.2-2):1, preferably (0.5-1.5):1, for example 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5 or 4:6.
[0053] In this invention, the raw material composition in the cathode material also includes raw materials conventional in the art.
[0054] In this invention, the cathode material is preferably lithium iron phosphate, lithium manganese iron phosphate, or sodium iron manganese phosphate.
[0055] In a preferred embodiment, the cathode material is lithium iron phosphate, and the raw material composition of the cathode material includes an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent; the carbon source includes a polymer and glucose.
[0056] The iron source can be of a type conventional in the art, such as iron phosphate. The lithium source can be of a type conventional in the art, such as lithium carbonate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The phosphorus source is generally added in the form of an aqueous phosphoric acid solution. The mass concentration of phosphoric acid in the aqueous phosphoric acid solution is preferably 75-90 wt%, for example, 85 wt%. The mass ratio of glucose to the polymer can be (0.2-2):1, more preferably (0.5-1.5):1, for example, 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5, or 4:6. The solvent can be of a type conventional in the art, such as water. The preferred mass ratio of the iron source, lithium source, phosphorus source and carbon source is (800-1200):(200-300):(3-9):(80-160), more preferably (900-1100):(210-240):(5-8):(100-140), for example 995:226:6.73:120, 995:226:6.73:130 or 995:226:6.73:110.
[0057] The raw material composition of the cathode material further includes a metal dopant. The metal dopant is preferably one or more of a Ti compound, a V compound, and a Nb compound, more preferably a Ti compound, such as titanium dioxide. The mass ratio of the metal dopant to the iron source is preferably (800-1200):(3-9), more preferably (900-1100):(5-7), for example 995:5.97.
[0058] In a preferred embodiment, the cathode material is lithium manganese iron phosphate, and the raw material composition of the cathode material includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent; the carbon source includes a polymer and glucose.
[0059] The lithium source can be of a type conventional in the art, such as lithium carbonate. The manganese source can be of a type conventional in the art, such as manganese acetate. The iron source can be of a type conventional in the art, such as ferrous oxalate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The mass ratio of glucose to the polymer can be (0.2-2):1, more preferably (0.5-1.5):1, for example 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5, or 4:6. The solvent can be of a type conventional in the art, such as anhydrous ethanol. The preferred mass ratio of the lithium source, manganese source, iron source, phosphorus source, carbon source and solvent is (200-500):(1000-1500):(5-15):(8-20):(50-150):(500-1500), more preferably (300-400):(150-300):(7-11):(10-15):(70-110):(800-1200), for example 350:1250:9:12:85:1000, 350:1250:9:12:90:1000 or 350:1250:9:12:100:1000.
[0060] In a preferred embodiment, the positive electrode material is sodium iron manganese phosphate, and the raw material composition of the positive electrode material includes a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent; the carbon source includes a polymer and glucose.
[0061] The sodium source can be conventional in the art, such as sodium carbonate. The phosphorus source can be conventional in the art, such as ammonium dihydrogen phosphate. The iron source can be conventional in the art, such as ferric oxide. The manganese source can be conventional in the art, such as manganese dioxide. The mass ratio of glucose to polymer can be (0.2-2):1, more preferably (0.5-1.5):1, for example 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5 or 4:6. The solvent can be conventional in the art, such as water. Based on sodium, iron, manganese and phosphorus elements, the molar ratio of sodium source, phosphorus source, iron source and manganese source is preferably (1-9):(1-5):(0.01-0.1):(1-9), more preferably (3-5):(2-4):(0.01-0.03):(3-5), for example 4:2.98:0.01:4. The molar ratio of the carbon source to the iron and manganese sources, calculated by carbon, iron and manganese elements, is preferably (0.2-1):(0.5-3), more preferably (0.3-1):(0.8-1.5), for example 0.5:1.
[0062] The present invention provides a method for preparing a cathode material, comprising the following steps: sintering a precursor slurry to obtain the cathode material; wherein the precursor slurry comprises the raw material composition of the cathode material as described above.
[0063] In this invention, the type of positive electrode material can be conventional in the art, such as lithium iron phosphate, lithium manganese iron phosphate, or sodium iron manganese phosphate.
[0064] In this invention, the sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h.
[0065] In this invention, the sintering is preferably carried out under an inert atmosphere, such as a nitrogen atmosphere.
[0066] In this invention, the heating rate from room temperature to the sintering temperature is preferably 1-10°C / min, more preferably 2-6°C / min, for example 3 or 5°C / min.
[0067] In this invention, the sintering is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.
[0068] The sintering temperature of the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time of the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature of the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.
[0069] The preferred temperature for the second-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the second stage is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is preferably 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.
[0070] In a preferred embodiment, the cathode material is lithium iron phosphate, and the preparation method of the cathode material includes the following steps: spray granulation and sintering of the precursor slurry; the precursor slurry includes an iron source, a lithium source, a phosphorus source, a carbon source and a solvent; the carbon source includes a polymer and glucose.
[0071] The iron source can be of a type conventional in the art, such as iron phosphate. The lithium source can be of a type conventional in the art, such as lithium carbonate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The phosphorus source is generally added in the form of an aqueous phosphoric acid solution. The mass concentration of phosphoric acid in the aqueous phosphoric acid solution is preferably 75-90 wt%, for example, 85 wt%. The mass ratio of glucose to the polymer can be (0.2-2):1, more preferably (0.5-1.5):1, for example, 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5, or 4:6. The solvent can be of a type conventional in the art, such as water. The preferred mass ratio of the iron source, lithium source, phosphorus source and carbon source is (800-1200):(200-300):(3-9):(80-160), more preferably (900-1100):(210-240):(5-8):(100-140), for example 995:226:6.73:120, 995:226:6.73:130 or 995:226:6.73:110.
[0072] The raw material composition of the cathode material further includes a metal dopant. The metal dopant is preferably one or more of a Ti compound, a V compound, and a Nb compound, more preferably a Ti compound, such as titanium dioxide. The mass ratio of the metal dopant to the iron source is preferably (800-1200):(3-9), more preferably (900-1100):(5-7), for example 995:5.97.
[0073] The solid content of the precursor slurry is preferably 30-60%, more preferably 35-50%, for example 40%. The D50 of the precursor slurry is preferably 250-500nm, more preferably 350-400nm, for example 370-380nm.
[0074] The precursor slurry is preferably obtained by mixing an iron source, a lithium source, a phosphorus source, a carbon source, and a solvent, followed by sand milling. The sand milling time is preferably 60-180 min, more preferably 90-150 min, for example 120 min.
[0075] The spray granulation temperature is preferably 180-300℃, more preferably 200-240℃, for example 220℃. During spray granulation, the flow rate of the precursor slurry is preferably 600-1000 ml / h, more preferably 700-900 ml / h, for example 800 ml / h.
[0076] The sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h. The heating rate from room temperature to the sintering temperature is preferably 1-10℃ / min, more preferably 2-6℃ / min, for example 3 or 5℃ / min.
[0077] In a preferred embodiment, the cathode material is lithium manganese iron phosphate, and the preparation method of the cathode material includes the following steps: sintering a precursor slurry; the precursor slurry includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent; the carbon source includes a polymer and glucose.
[0078] The lithium source can be of a type conventional in the art, such as lithium carbonate. The manganese source can be of a type conventional in the art, such as manganese acetate. The iron source can be of a type conventional in the art, such as ferrous oxalate. The phosphorus source can be of a type conventional in the art, such as phosphoric acid. The mass ratio of glucose to the polymer can be (0.2-2):1, more preferably (0.5-1.5):1, for example 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5, or 4:6. The solvent can be of a type conventional in the art, such as anhydrous ethanol. The preferred mass ratio of the lithium source, manganese source, iron source, phosphorus source, carbon source and solvent is (200-500):(1000-1500):(5-15):(8-20):(50-150):(500-1500), more preferably (300-400):(150-300):(7-11):(10-15):(70-110):(800-1200), for example 350:1250:9:12:85:1000, 350:1250:9:12:90:1000 or 350:1250:9:12:100:1000.
[0079] The precursor slurry is preferably obtained by ball milling a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source, and a solvent. The ball milling speed is preferably 200-400 r / min, more preferably 250-300 r / min, for example, 280 r / min. The ball milling time is preferably 1-7 h, more preferably 3-5 h, for example, 4 h. The ball-to-material ratio during ball milling is preferably (4-12):1, more preferably (6-10):1, for example, 8:1.
[0080] Prior to sintering, the precursor slurry preferably undergoes a process of solvent removal and particle size control. The solvent removal method can be conventional in the art, such as vacuum drying. The vacuum drying temperature is preferably 40-70°C, more preferably 50-60°C, for example 55°C. The vacuum drying time is preferably 5-12 hours, more preferably 6-10 hours, for example 8 hours. The particle size control method can be conventional in the art, such as grinding. The endpoint of particle size control is preferably that the material can pass through a 100-mesh sieve.
[0081] The sintering process is preferably divided into a single-stage sintering and a two-stage sintering, wherein the temperature of the two-stage sintering is higher than that of the single-stage sintering.
[0082] The sintering temperature for the first stage is preferably 300-600℃, more preferably 400-500℃, for example 480℃. The sintering time for the first stage is preferably 1-4h, more preferably 2-3h, for example 2h. The heating rate from room temperature to the sintering temperature for the first stage is preferably 3-8℃ / min, more preferably 4-6℃ / min, for example 5℃ / min.
[0083] The preferred temperature for the two-stage sintering is 500-850℃, more preferably 650-750℃, for example 700℃. The preferred sintering time for the two stages is 5-10 hours, more preferably 7-9 hours, for example 8 hours. The preferred heating rate from the temperature of the first-stage sintering to the temperature of the second-stage sintering is 1-5℃ / min, more preferably 2-4℃ / min, for example 3℃ / min.
[0084] In a preferred embodiment, the cathode material is sodium iron manganese phosphate, and the preparation method of the cathode material includes the following steps: spray granulation and sintering of the precursor slurry; the precursor slurry includes a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source and a solvent; the carbon source includes a polymer and glucose.
[0085] The sodium source can be conventional in the art, such as sodium carbonate. The phosphorus source can be conventional in the art, such as ammonium dihydrogen phosphate. The iron source can be conventional in the art, such as ferric oxide. The manganese source can be conventional in the art, such as manganese dioxide. The mass ratio of glucose to polymer can be (0.2-2):1, more preferably (0.5-1.5):1, for example 1:1, 1.2:1, 6:7, 0.8:1, 4:4.5 or 4:6. The solvent can be conventional in the art, such as water. Based on sodium, iron, manganese and phosphorus elements, the molar ratio of sodium source, phosphorus source, iron source and manganese source is preferably (1-9):(1-5):(0.01-0.1):(1-9), more preferably (3-5):(2-4):(0.01-0.03):(3-5), for example 4:2.98:0.01:4. The molar ratio of the carbon source to the iron and manganese sources, calculated by carbon, iron and manganese elements, is preferably (0.2-1):(0.5-3), more preferably (0.3-1):(0.8-1.5), for example 0.5:1.
[0086] The solid content of the precursor slurry is preferably 30-60 wt%, more preferably 45-55 wt%, for example 50 wt%.
[0087] The precursor slurry is preferably obtained by mixing a sodium source, a phosphorus source, an iron source, a manganese source, a carbon source, and a solvent, followed by sand milling. The sand milling speed is preferably 1400-2600 r / min, more preferably 1800-2200 r / min, for example, 2000 r / min. The sand milling time is preferably 3-10 h, more preferably 5-7 h, for example, 6 h.
[0088] The preferred temperature for spray granulation is 180-300℃, more preferably 200-240℃, such as 250℃.
[0089] The sintering temperature can be 300-850℃, preferably 400-750℃, for example 480, 550, 700 or 720℃. The sintering time can be 1-20h, preferably 2-13h, for example 2, 7, 8, 10 or 12h. The heating rate from room temperature to the sintering temperature is preferably 1-10℃ / min, more preferably 2-6℃ / min, for example 3 or 5℃ / min.
[0090] In this invention, polyether segments, aromatic rings, and nitrile groups are introduced into the carbon source molecular structure. The introduction of polyether segments improves the polymer's solubility in water, making it suitable for preparing aqueous or alcohol-based cathode materials, thus compensating for the mismatch between benzene rings, nitrile groups, and solvents (water or alcohol). The introduction of aromatic rings can increase the carbon content on the cathode material surface, reducing the amount of carbon source added and the raw material cost of the cathode material. Moreover, as a rigid structure, aromatic rings are more likely to generate ordered graphitized coated carbon on the cathode material surface. The introduction of nitrile groups promotes the formation of cyclic structures during the carbon source's pyrolysis process, thereby generating ordered coated carbon on the cathode material surface.
[0091] This invention provides a cathode material, which is prepared using the cathode material preparation method described above.
[0092] The present invention provides an electrode sheet comprising the positive electrode material as described above.
[0093] The present invention provides a battery comprising the electrodes as described above.
[0094] In this invention, the battery may be a lithium-ion battery or a sodium-ion battery.
[0095] The positive and progressive effects of this invention are as follows: The cathode material prepared using the polymer of this application as a carbon source has low powder resistivity, high electrical conductivity and good compaction density; the battery made from this cathode material has excellent electrochemical performance. Attached Figure Description
[0096] Figure 1 The infrared spectrum of polymer 1 obtained in Example 1 is shown.
[0097] Figure 2 The infrared spectrum of polymer 2 obtained in Example 2 is shown.
[0098] Figure 3 The infrared spectrum of polymer 3 obtained in Example 3 is shown.
[0099] Figure 4 The infrared spectrum of polymer 4 obtained in Example 4 is shown.
[0100] Figure 5 The image shows the GPC spectrum of polymer 1 obtained in Example 1.
[0101] Figure 6 The image shows the GPC spectrum of polymer 2 obtained in Example 2.
[0102] Figure 7 The image shows the GPC spectrum of polymer 3 obtained in Example 3.
[0103] Figure 8The image shows the GPC spectrum of polymer 4 obtained in Example 4.
[0104] Figure 9 The image shows a SEM image of the cathode material prepared using the cathode material obtained in Example 1.
[0105] Figure 10 The image shows a SEM image of the cathode material prepared using the cathode material obtained in Comparative Example 1. Detailed Implementation
[0106] The present invention will be further illustrated by way of embodiments below, but the present invention is not limited to the scope of the embodiments described herein.
[0107] I. Preparation of Lithium Iron Phosphate Cathode Material
[0108] Example 1
[0109] 1. Polymer preparation: (1) Add 1 mol of unsaturated polyether monomer (methyl allyl alcohol polyoxyethylene ether HPEG2400) to a reactor equipped with a stirrer and a heater, add solvent (ethyl acetate), turn on the stirrer at a speed of 500 r / min, heat to 45°C, and after HPEG2400 is completely dissolved, a bottom liquid is obtained with a mass concentration of 50%; (2) Prepare a solution A with a mass concentration of 50% by mixing unsaturated aromatic monomer (styrene), unsaturated nitrile monomer (acrylonitrile), acrylic acid compound (acrylic acid) and solvent (ethyl acetate); prepare a solution B with a mass concentration of 2.0% by mixing chain transfer agent (mercaptoethanol), reducing agent (vitamin E) and solvent (ethyl acetate); the molar ratio of HPEG2400, styrene, acrylonitrile and acrylic acid is 1.0:2.0:1.5:2.5, the amount of mercaptoethanol is 0.5% of the total mass of HPEG2400, styrene, acrylonitrile and acrylic acid, and the total amount of ethyl acetate in solutions A and B is 1.25 times the total mass of HPEG2400, styrene, acrylonitrile and acrylic acid; (3) Add an initiator (hydrogen peroxide) to the base liquid. The amount of hydrogen peroxide is 0.3% of the total mass of HPEG2400, styrene, acrylonitrile and acrylic acid. The molar ratio of hydrogen peroxide to vitamin E is 5.3:1.0. At the same time, add solution A and solution B dropwise at a uniform rate. The dropwise addition time of solution A is 60 min and the dropwise addition time of solution B is 75 min. The volume ratio of solution A to solution B is 40:10. The temperature of the polymerization reaction is controlled at 30-50℃. After the dropwise addition is completed, the polymerization reaction is carried out under the heat preservation state for 80 min. The heat preservation temperature is 50℃. After the polymerization reaction is completed, the vacuum is drawn at -95kPa pressure for 90 min to remove the residual unreacted monomers. The vacuum is stopped to obtain polymer carbon source 1.
[0110] 2. Preparation of lithium iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 1 and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant; wherein, the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the polymer carbon source accounts for 50% of the mass percentage of carbon source. 995 parts of iron phosphate, 226 parts of lithium carbonate, 6.73 parts of 85%wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 60 parts of polymer carbon source 1 were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.
[0111] The obtained lithium iron phosphate material was crushed to powder with a particle size D50 of 1.2-1.3 μm using a traditional Chinese medicine crusher. The traditional Chinese medicine crusher was a Teruis traditional Chinese medicine pulverizer, and the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.
[0112] Example 2
[0113] 1. Polymer preparation: (1) Add 1 mol of unsaturated polyether monomer (methyl allyl alcohol polyoxyethylene ether HPEG2400) to a reactor equipped with a stirrer and a heater, add solvent (ethyl acetate), turn on the stirrer at a speed of 500 r / min, heat to 40 °C, and after HPEG2400 is completely dissolved, a bottom liquid is obtained with a mass concentration of 55%; (2) Prepare a solution A with a mass concentration of 40% by mixing unsaturated aromatic monomer (styrene), unsaturated nitrile monomer (acrylonitrile), acrylic compound (methyl acrylate) and solvent (ethyl acetate); prepare a solution B with a mass concentration of 1.8% by mixing chain transfer agent (tert-dodecyl mercaptan), reducing agent (vitamin C) and solvent (ethyl acetate); the molar ratio of HPEG2400, styrene, acrylonitrile and methyl acrylate is 1.0:3.0:1.0:3.0, the amount of tert-dodecyl mercaptan is 0.7% of the total mass of HPEG2400, styrene, acrylonitrile and methyl acrylate, and the total amount of ethyl acetate in solutions A and B is 1.0 times the total mass of HPEG2400, styrene, acrylonitrile and methyl acrylate; (3) Add an initiator (ammonium persulfate) to the base liquid. The amount of ammonium persulfate is 0.2% of the total mass of HPEG2400, styrene, acrylonitrile and methyl acrylate. The molar ratio of ammonium persulfate to vitamin C is 5.0:1.0. At the same time, add solution A and solution B dropwise at a uniform rate for reaction. The dropwise addition time of solution A is 55 min and the dropwise addition time of solution B is 70 min. The temperature of the polymerization reaction is controlled at 30-50℃. After the dropwise addition is completed, the polymerization reaction is carried out under the heat preservation state for 60 min at the heat preservation temperature of 45℃. After the polymerization reaction is completed, the vacuum is drawn at -97 kPa pressure for 70 min. The vacuum is stopped to remove the residual unreacted monomers and obtain polymer carbon source 2.
[0114] 2. Preparation of lithium iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 2 and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant; wherein, the mass percentage of carbon source in the raw material composition of the cathode material is 8.2%; and the mass percentage of polymer carbon source is 45.5%; 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85%wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 50 parts of polymer carbon source 2 were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.
[0115] Example 3
[0116] 1. Polymer preparation: (1) Add 1 mol of unsaturated polyether monomer (isoprenol polyoxyethylene ether TPEG2400) to a reactor equipped with a stirrer and a heater, add solvent (ethyl acetate), turn on the stirrer at a speed of 500 r / min, heat to 50 °C, and obtain the bottom liquid after TPEG2400 is completely dissolved. The bottom liquid has a mass concentration of 60%. (2) Prepare a solution A with a mass concentration of 40% by mixing unsaturated aromatic monomer (styrene), unsaturated nitrile monomer (acrylonitrile), acrylic compound (methacrylic acid) and solvent (ethyl acetate); prepare a solution B with a mass concentration of 2.5% by mixing chain transfer agent (mercaptoethanol), reducing agent (vitamin E) and solvent (ethyl acetate); the molar ratio of TPEG2400, styrene, acrylonitrile and methacrylic acid is 1.0:2.5:1.5:2.0, the amount of mercaptoacetic acid is 0.6% of the total mass of TPEG2400, styrene, acrylonitrile and methacrylic acid, and the amount of ethyl acetate in solutions A and B is 1.5 times the total mass of TPEG2400, styrene, acrylonitrile and methacrylic acid; (3) Add an initiator (cumene hydrogen peroxide) to the base liquid. The amount of cumene hydrogen peroxide is 0.25% of the total mass of TPEG2400, styrene, acrylonitrile and methacrylic acid. The molar ratio of cumene hydrogen peroxide to vitamin E is 4.5:1.0. At the same time, add solution A and solution B dropwise at a uniform rate for reaction. The dropwise addition time of solution A is 70 min and the dropwise addition time of solution B is 85 min. The temperature of the polymerization reaction is controlled at 30-50℃. After the dropwise addition is completed, the polymerization reaction is carried out under the heat preservation state for 90 min at the heat preservation temperature of 50℃. After the polymerization reaction is completed, the vacuum is drawn under the pressure of -100kPa for 30 min to remove the residual unreacted monomers. The vacuum is stopped to obtain polymer carbon source 3.
[0117] 2. Preparation of lithium iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 3 and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant. The carbon source accounts for 9.5% of the total carbon source composition, and the polymer carbon source accounts for 53.8% of the total carbon source composition. 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85%wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 70 parts of polymer carbon source 3 were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.
[0118] Example 4
[0119] 1. Polymer preparation: (1) Add 1 mol of unsaturated polyether monomer (isoprenol polyoxyethylene ether TPEG2400) to a reactor equipped with a stirrer and a heater, add solvent (ethyl acetate), turn on the stirrer, heat to 45°C, stir at a speed of 500 r / min, and obtain the bottom liquid after TPEG2400 is completely dissolved. The bottom liquid has a mass concentration of 40%. (2) Prepare a solution A with a mass concentration of 60% by mixing unsaturated aromatic monomer (styrene), unsaturated nitrile monomer (acrylonitrile), acrylic compound (methyl methacrylate) and solvent (ethyl acetate); prepare a solution B with a mass concentration of 1.7% by mixing chain transfer agent (n-dodecyl mercaptan), reducing agent (vitamin C) and solvent (ethyl acetate); the molar ratio of TPEG2400, styrene, acrylonitrile and methyl methacrylate is 1.0:1.0:2.5:2.5, the amount of n-dodecyl mercaptan is 0.8% of the total mass of TPEG2400, styrene, acrylonitrile and methyl methacrylate, and the amount of ethyl acetate in solutions A and B is twice the total mass of TPEG2400, styrene, acrylonitrile and methyl methacrylate; (3) Add an initiator (hydrogen peroxide) to the base liquid. The amount of hydrogen peroxide is 0.19% of the total mass of TPEG2400, styrene, acrylonitrile and methyl methacrylate. The molar ratio of cumene hydrogen peroxide and vitamin C is 5.8:1.0. At the same time, add solution A and solution B dropwise at a uniform rate. The dropwise addition time of solution A is 60 min and the dropwise addition time of solution B is 70 min. The temperature of the polymerization reaction is controlled at 30-50℃. After the dropwise addition is completed, the polymerization reaction is carried out for 100 min under the heat preservation state. The heat preservation temperature is 45℃. After the polymerization reaction is completed, the vacuum is drawn for 50 min under a pressure of -98 kPa to remove the residual unreacted monomers. The vacuum is stopped to obtain polymer carbon source 4.
[0120] 2. Preparation of lithium iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 4 and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant. The carbon source accounts for 9.5% of the total carbon source composition, and the polymer carbon source accounts for 53.8% of the total carbon source composition. 995 parts of iron phosphate, 226 parts of lithium carbonate, 6.73 parts of 85% wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 70 parts of polymer carbon source 4 were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.
[0121] Example 5
[0122] The only difference from Example 1 is that the unsaturated polyether monomer (methyl allyl alcohol polyoxyethylene ether HPEG2400) in the preparation of the polymer (1) is replaced with isopentenyl alcohol polyoxyethylene ether TPEG2400.
[0123] Example 6
[0124] The only difference from Example 1 is that the unsaturated aromatic monomer (styrene) in the preparation of the polymer (1) is replaced with vinyltoluene.
[0125] Example 7
[0126] The only difference from Example 1 is that the unsaturated nitrile monomer (acrylonitrile) in the preparation of the polymer (1) is replaced with methacrylonitrile.
[0127] Example 8
[0128] The only difference from Example 1 is that the acrylic compound (acrylic acid) in the preparation of the polymer (1) is replaced with hydroxyethyl acrylate.
[0129] Example 9
[0130] The only difference from Example 1 is that the unsaturated polyether monomer (methyl allyl alcohol polyoxyethylene ether HPEG2400) in the preparation of the polymer (1) is replaced with allyl polyoxyethylene ether APEG2400, and the unsaturated nitrile monomer (acrylonitrile) is replaced with methacrylonitrile.
[0131] Example 10
[0132] The only difference from Example 1 is that the molar ratio of HPEG2400, styrene, acrylonitrile and acrylic acid is 1.0:1.0:2.5:2.5.
[0133] Example 11
[0134] The only difference from Example 1 is that glucose is replaced with polyethylene glycol PEG1500 in the preparation of the lithium iron phosphate cathode material, and the amount added is 60 parts.
[0135] Comparative Example 1
[0136] The only difference from Example 1 is that: the polymer carbon source 1 is replaced with polyethylene glycol PEG1500, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of polymer carbon source in carbon source is 0%.
[0137] Comparative Example 2
[0138] The only difference from Example 1 is that: the polymer carbon source 1 is replaced with polyethylene glycol PEG6000, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of polymer carbon source in carbon source is 0%.
[0139] Comparative Example 3
[0140] 1. Polymer preparation: The synthesis process of the polymer was the same as in Example 1, except that the unsaturated polyether monomer (methyl allyl alcohol polyoxyethylene ether HPEG2400) was not added as the synthetic monomer. (1) Prepare a solution A with a mass concentration of 50% by mixing unsaturated aromatic monomer (styrene), unsaturated nitrile monomer (acrylonitrile), acrylic compound (acrylic acid) and solvent (ethyl acetate). Turn on the stirrer, heat to 45°C, and stir at a speed of 500 r / min. Prepare a solution B with a mass concentration of 2.0% by mixing chain transfer agent (mercaptoethanol), reducing agent (vitamin E) and solvent (ethyl acetate). The molar ratio of styrene, acrylonitrile and acrylic acid is 2.0:1.5:2.5. The amount of mercaptoethanol used is 0.5% of the total mass of styrene, acrylonitrile and acrylic acid. The total amount of ethyl acetate used in solutions A and B is 1.25 times the total mass of styrene, acrylonitrile and acrylic acid. (2) Add an initiator (hydrogen peroxide) to the base liquid. The amount of hydrogen peroxide is 0.3% of the total mass of styrene, acrylonitrile and acrylic acid. The molar ratio of hydrogen peroxide to vitamin E is 5.3:1.0. At the same time, add solution A and solution B dropwise at a uniform rate. The dropwise addition time of solution A is 60 min and the dropwise addition time of solution B is 75 min. The temperature of the polymerization reaction is controlled at 30-50℃. After the dropwise addition is completed, the polymerization reaction is carried out under the heat preservation state for 80 min at a heat preservation temperature of 50℃. After the polymerization reaction is completed, vacuum is applied at a pressure of -95 kPa for 90 min to remove the residual unreacted monomers. The vacuum is then stopped to obtain polymer carbon source 5.
[0141] 2. Preparation of lithium iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 5 and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant; wherein, the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the polymer carbon source accounts for 50% of the mass percentage of carbon source. 995 parts of iron phosphate, 226 parts of lithium carbonate, 6.73 parts of 85% wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 60 parts of polymer carbon source 5 were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.
[0142] The obtained lithium iron phosphate material was crushed to powder with a particle size D50 of 1.2-1.3 μm using a traditional Chinese medicine crusher. The traditional Chinese medicine crusher was a Teruis traditional Chinese medicine pulverizer, and the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.
[0143] Comparative Example 4
[0144] 1. Polymer preparation: The synthesis process of the polymer was the same as in Example 1, except that the unsaturated aromatic monomer (styrene) was not added as the synthetic monomer. (1) Add 1 mol of unsaturated polyether monomer (methyl allyl alcohol polyoxyethylene ether HPEG2400) to a reactor equipped with a stirrer and a heater, add solvent (ethyl acetate), turn on the stirrer at a speed of 500 r / min, heat to 45°C, and after HPEG2400 is completely dissolved, a bottom liquid is obtained with a mass concentration of 50%; (2) Prepare a solution A with a mass concentration of 50% by mixing unsaturated nitrile monomer (acrylonitrile), acrylic compound (acrylic acid) and solvent (ethyl acetate), and prepare a solution B with a mass concentration of 2.0% by mixing chain transfer agent (mercaptoethanol), reducing agent (vitamin E) and solvent (ethyl acetate). The molar ratio of HPEG2400, acrylonitrile and acrylic acid is 1.0:2.0:1.5:2.5. The amount of mercaptoethanol is 0.5% of the total mass of HPEG2400, acrylonitrile and acrylic acid. The amount of ethyl acetate in solutions A and B is 1.25 times the total mass of HPEG2400, acrylonitrile and acrylic acid. (3) Add an initiator (hydrogen peroxide) to the base liquid. The amount of hydrogen peroxide is 0.3% of the total mass of HPEG2400, acrylonitrile and acrylic acid. The molar ratio of hydrogen peroxide to vitamin E is 5.3:1.0. At the same time, add solution A and solution B dropwise at a uniform rate. The dropwise addition time of solution A is 60 min and the dropwise addition time of solution B is 75 min. The temperature of the polymerization reaction is controlled at 30-50℃. After the dropwise addition is completed, the polymerization reaction is carried out under the heat preservation state for 80 min at a heat preservation temperature of 50℃. After the polymerization reaction is completed, vacuum is applied at a pressure of -95 kPa for 90 min to remove the residual unreacted monomers. The vacuum is then stopped to obtain polymer carbon source 6.
[0145] 2. Preparation of lithium iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 6 and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant; wherein, the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the mass percentage of polymer carbon source is 50% of the total carbon source. 995 parts of iron phosphate, 226 parts of lithium carbonate, 6.73 parts of 85%wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 60 parts of polymer carbon source 6 were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.
[0146] The obtained lithium iron phosphate material was crushed to powder with a particle size D50 of 1.2-1.3 μm using a traditional Chinese medicine crusher. The traditional Chinese medicine crusher was a Teruis traditional Chinese medicine pulverizer, and the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.
[0147] Comparative Example 5
[0148] 1. Polymer preparation: The only difference is that the unsaturated nitrile monomer (acrylonitrile) is not added as the synthetic monomer; all other conditions are the same as in Example 1. The specific polymer synthesis process is as follows: (1) Add 1 mol of unsaturated polyether monomer (methyl allyl alcohol polyoxyethylene ether HPEG2400) to a reactor equipped with a stirrer and a heater, add solvent (ethyl acetate), turn on the stirrer at a speed of 500 r / min, heat to 45°C, and after HPEG2400 is completely dissolved, a bottom liquid is obtained with a mass concentration of 50%; (2) Prepare a solution A with a mass concentration of 50% by mixing unsaturated aromatic monomer (styrene), acrylic acid compound (acrylic acid) and solvent (ethyl acetate), and prepare a solution B with a mass concentration of 2.0% by mixing chain transfer agent (mercaptoethanol), reducing agent (vitamin E) and solvent (ethyl acetate). The molar ratio of HPEG2400, styrene and acrylic acid is 1.0:2.0:1.5:2.5. The amount of mercaptoethanol used is 0.5% of the total mass of HPEG2400, styrene and acrylic acid. The total amount of ethyl acetate used in solutions A and B is 1.25 times the total mass of HPEG2400, styrene and acrylic acid. (3) Add an initiator (hydrogen peroxide) to the base liquid. The amount of hydrogen peroxide is 0.3% of the total mass of HPEG2400, styrene and acrylic acid. The molar ratio of hydrogen peroxide to vitamin E is 5.3:1.0. At the same time, add solution A and solution B dropwise at a uniform rate. The dropwise addition time of solution A is 60 min and the dropwise addition time of solution B is 75 min. The temperature is controlled at 30-50℃ during the reaction. After the dropwise addition is completed, keep the reaction at 50℃ for 80 min. After the reaction is completed, vacuum at -95 kPa pressure for 90 min to remove the residual unreacted monomers. Stop the vacuum to obtain polymer carbon source 7.
[0149] 2. Preparation of lithium iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 7 and glucose as carbon sources; iron phosphate, lithium carbonate, and phosphoric acid aqueous solution as iron source, lithium source, and phosphorus source, respectively; and titanium dioxide as a metal dopant; wherein, the mass percentage of carbon source in the raw material composition of the cathode material is 8.9%; and the polymer carbon source accounts for 50% of the mass percentage of carbon source. 995 parts of ferric phosphate, 226 parts of lithium carbonate, 6.73 parts of 85%wt phosphoric acid aqueous solution, 5.97 parts of titanium dioxide, 60 parts of glucose and 60 parts of polymer carbon source 7 were added to a sand mill (WSP-0.5 of Changzhou Longxin Intelligent Equipment Co., Ltd.) and water was added. The mixture was sand milled for 120 minutes to obtain a precursor slurry with a solid content of 40% and a particle size D50 of 370-380nm. The precursor slurry was spray-granulated in a spray granulation equipment (SP1500 from Shanghai Shunyi Experimental Equipment Co., Ltd.), with an inlet temperature of 220℃ and a material flow rate of 800ml / h. The spray-granulated powder was sintered (using a QLYF-4-1200 sintering equipment from Shanghai Jingzhao Machinery Equipment Co., Ltd.), with a heating rate of 3℃ / min to 720℃ and a holding time of 7h to obtain lithium iron phosphate material.
[0150] The obtained lithium iron phosphate material was crushed to powder with a particle size D50 of 1.2-1.3 μm using a traditional Chinese medicine crusher. The traditional Chinese medicine crusher was a Teruis traditional Chinese medicine pulverizer, and the particle size was tested using a Malvern Panaco Mastersizer-3000 laser particle size analyzer.
[0151] II. Preparation of Lithium Manganese Iron Phosphate Materials
[0152] Example 12
[0153] 1. Polymer preparation: Same as Example 1.
[0154] 2. Preparation of lithium manganese iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 1 and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.3%; the polymer carbon source accounts for 55.6% of the mass percentage of carbon source; 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 50 parts polymer carbon source 1, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain the precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.
[0155] Example 13
[0156] 1. Polymer preparation: Same as Example 2.
[0157] 2. Preparation of lithium manganese iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 2 and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.0%; the polymer carbon source accounts for 52.9% of the mass percentage of carbon source; 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 45 parts polymer carbon source 2, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain the precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.
[0158] Example 14
[0159] 1. Polymer preparation: Same as Example 3.
[0160] 2. Preparation of lithium manganese iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 3 and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; the polymer carbon source accounts for 60% of the mass percentage of carbon source; 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 60 parts polymer carbon source, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 to obtain a precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.
[0161] Example 15
[0162] 1. Polymer preparation: Same as Example 4.
[0163] 2. Preparation of lithium manganese iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 4 and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; the polymer carbon source accounts for 60% of the mass percentage of carbon source. 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 60 parts polymer carbon source, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain the precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.
[0164] Comparative Example 6
[0165] The only difference from Example 12 is that: the polymer carbon source 1 is replaced with polyethylene glycol PEG1500, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; and the mass percentage of polymer carbon source in carbon source is 0%.
[0166] Comparative Example 7
[0167] The only difference from Example 12 is that: the polymer carbon source 1 is replaced with polyethylene glycol PEG6000, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; and the mass percentage of polymer carbon source in carbon source is 0%.
[0168] Comparative Example 8
[0169] 1. Polymer preparation: Same as comparison 3.
[0170] 2. Preparation of lithium manganese iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 5 and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; the polymer carbon source accounts for 60% of the mass percentage of carbon source; 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 60 parts polymer carbon source, 5 parts phosphoric acid, 12 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain the precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.
[0171] Comparative Example 9
[0172] 1. Polymer preparation: Same as comparison 4.
[0173] 2. Preparation of lithium manganese iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 6 and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; the polymer carbon source accounts for 60% of the mass percentage of carbon source. 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 60 parts polymer carbon source, 12 parts phosphoric acid, and 1000 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 to obtain a precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.
[0174] Comparative Example 10
[0175] 1. Polymer preparation: Same as the comparison ratio 5.
[0176] 2. Preparation of lithium manganese iron phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 7 and glucose as carbon sources; lithium carbonate, manganese acetate, ferrous oxalate and phosphoric acid as lithium source, manganese source, iron source and phosphorus source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 5.8%; the polymer carbon source accounts for 60% of the mass percentage of carbon source. 350 parts lithium carbonate, 1250 parts manganese acetate, 9 parts ferrous oxalate, 40 parts glucose, 60 parts polymer carbon source, 7 parts phosphoric acid, 12 parts anhydrous ethanol were added to an agate ball mill jar and ball-milled for 4 hours at a ball-to-material ratio of 8:1 at a speed of 280 r / min to obtain the precursor slurry. The obtained precursor slurry was transferred to an evaporating dish and vacuum dried at 55°C for 8 hours. After grinding through a 100-mesh sieve, it was placed in a tube furnace and argon gas was introduced at a flow rate of 50 mL / min for 30 minutes. The temperature was first increased to 480°C at a rate of 5°C / min and held for 2 hours. Then, the temperature was increased to 700°C at a rate of 3°C / min and held for 8 hours. After sintering, the argon atmosphere was maintained and the mixture was allowed to cool naturally to room temperature. The mixture was then ground in an agate mortar and passed through a 200-mesh sieve to obtain lithium manganese iron phosphate material.
[0177] III. Preparation of Sodium Iron Manganese Phosphate Cathode Material for Sodium-Ion Batteries
[0178] Example 16
[0179] 1. Polymer preparation: Same as Example 1.
[0180] 2. Preparation of sodium iron manganese phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 1 and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide as sodium source, phosphorus source, iron source, and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; the polymer carbon source accounts for 50% of the mass percentage of carbon source; Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polymer carbon source 1 were mixed at a mass ratio of 1:1 as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled to be 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at a speed of 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.
[0181] Example 17
[0182] 1. Polymer preparation: Same as Example 2.
[0183] 2. Preparation of sodium iron manganese phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 2 and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide and manganese dioxide as sodium source, phosphorus source, iron source and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; the polymer carbon source accounts for 50% of the mass percentage of carbon source; Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polymer carbon source 2 were mixed in a 1:1 ratio as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.
[0184] Example 18
[0185] 1. Polymer preparation: Same as Example 3.
[0186] 2. Preparation of sodium iron manganese phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 3 and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide as sodium source, phosphorus source, iron source, and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; the polymer carbon source accounts for 50% of the mass percentage of carbon source; Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polymer carbon source 3 were mixed in a 1:1 ratio as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.
[0187] Example 19
[0188] 1. Polymer preparation: Same as Example 4.
[0189] 2. Preparation of sodium iron manganese phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 4 and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide as sodium source, phosphorus source, iron source, and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; the polymer carbon source accounts for 50% of the mass percentage of carbon source; Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polymer carbon source 4 were mixed in a 1:1 ratio as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.
[0190] Comparative Example 11
[0191] The only difference from Example 16 is that: the polymer carbon source 1 is replaced with polyethylene glycol PEG1500, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the mass percentage of polymer carbon source in carbon source is 0%.
[0192] Comparative Example 12
[0193] The only difference from Example 16 is that: the polymer carbon source 1 is replaced with polyethylene glycol PEG6000, and the amount added is 60 parts; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; and the polymer carbon source accounts for 0% of the mass percentage of carbon source.
[0194] Comparative Example 13
[0195] 1. Polymer preparation: Same as comparison 3.
[0196] 2. Preparation of sodium iron manganese phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 5 and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide as sodium source, phosphorus source, iron source, and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; the polymer carbon source accounts for 50% of the mass percentage of carbon source; Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polymer carbon source 5 were mixed in a 1:1 ratio as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.
[0197] Comparative Example 14
[0198] 1. Polymer preparation: Same as comparison 4.
[0199] 2. Preparation of sodium iron manganese phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 6 and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide as sodium source, phosphorus source, iron source, and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; the polymer carbon source accounts for 50% of the mass percentage of carbon source; Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polymer carbon source 6 were mixed in a 1:1 ratio as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.
[0200] Comparative Example 15
[0201] 1. Polymer preparation: Same as the comparison ratio 5.
[0202] 2. Preparation of sodium iron manganese phosphate cathode material: The raw material composition of the cathode material includes: polymer carbon source 7 and glucose as carbon sources; sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide as sodium source, phosphorus source, iron source, and manganese source, respectively; the mass percentage of carbon source in the raw material composition of the cathode material is 12%; the polymer carbon source accounts for 50% of the mass percentage of carbon source; Sodium carbonate, ammonium dihydrogen phosphate, ferric oxide, and manganese dioxide were used as sodium, phosphorus, iron, and manganese sources, respectively. Glucose and polymer carbon source 7 were mixed in a 1:1 ratio as the carbon source. The molar ratio of sodium, iron, manganese, and phosphorus in the raw materials was controlled at 4:2.98:0.01:4, and the ratio of the molar amount of carbon source (calculated as carbon) to the sum of the molar amounts of iron and manganese was 0.5:1. The raw materials were put into a sand mill and ground at 2000 r / min for 6 h, with a solid content of 50 wt% during grinding. The mixture was prepared into a dry precursor powder at 250 °C using a spray drying method. The precursor powder was placed in a box furnace and calcined at 550 °C for 12 h under a N2 atmosphere, followed by natural cooling to obtain the cathode material.
[0203] Example 1
[0204] 1. Structural characterization
[0205] The polymers obtained in Examples 1-4 were subjected to infrared spectroscopy. A Nicolet iG50 FTIR spectrometer was used. ATR mode was activated, and the air background was tested. The polymer was dropped onto a diamond crystal on the ATR module, and the sample was taken at 400 cm⁻¹. -1 -4000cm -1 The area was scanned 32 times, with a resolution of 4cm. -1 The result is as follows Figure 1-4 As shown. Figure 1 The infrared spectrum of the polymer obtained in Example 1 is shown below. Figure 2 The infrared spectrum of the polymer obtained in Example 2; Figure 3 The infrared spectrum of the polymer obtained in Example 3; Figure 4 The image shows the infrared spectrum of the polymer obtained in Example 4.
[0206] Depend on Figures 1-4 It can be seen that the polymer carbon source is at 2863 cm⁻¹. -1 Nearby, there is a peak representing the CH symmetric stretching vibration, at 1737 cm⁻¹. -1 The presence of a stretching vibration characteristic peak representing the C=O group nearby indicates the presence of an acrylic acid unit; at 2237 cm⁻¹ -1 Nearby, there is a vibrational peak representing the C≡N stretching vibration, indicating the presence of acrylonitrile units; at 1452 cm⁻¹ -1 Nearby, there are vibrational peaks representing the benzene ring skeleton, indicating the presence of styrene units; at 1095 cm⁻¹ -1 The nearby peaks represent COC stretching vibrations, indicating the PEG segments on HPEG2400. These results demonstrate the successful synthesis of the polymer.
[0207] 2. Molecular weight and PDI testing
[0208] The molecular weight and PDI of the polymers prepared in Examples 1-4 were determined using Waters 1515 gel permeation chromatography (GPC) and a Waters 2414 refractive index detector.
[0209] The test method was as follows: Approximately 5-10 mg of polymer was accurately weighed and dissolved in 10 mL of mobile phase (0.01 mol / L NaNO3 aqueous solution). The sample was filtered through a 0.45 μm aqueous filter membrane and injected. Polyethylene glycol (PEG) of different molecular weights was used as standard samples to generate a standard curve, and the chromatogram results were processed. The results are as follows: Figure 5-8 As shown, Figure 5 The GPC diagram of the polymer obtained in Example 1; Figure 6 The GPC diagram of the polymer obtained in Example 2; Figure 7 The GPC diagram of the polymer obtained in Example 3; Figure 8 The image shows the GPC diagram of the polymer obtained in Example 4. According to the results, the weight-average molecular weights of the polymers obtained in Examples 1-4 were 36118, 42282, 38100, and 35397, respectively, and the PDIs were 2.039820, 1.799366, 1.706434, and 1.850811, respectively.
[0210] Example 2
[0211] 1. The residual carbon content of the lithium iron phosphate materials prepared in the examples and comparative examples was tested using a Shanghai Dekai HCS-140 high-frequency infrared carbon-sulfur analyzer.
[0212] 2. The powder resistivity and compaction density of lithium iron phosphate materials prepared in the examples and comparative examples were tested using Xiamen Yuaneng four-probe powder resistivity PRCD2110.
[0213] The test results are shown in Table 1.
[0214] 3. Microscopic morphological observation
[0215] The surface morphology of lithium iron phosphate materials prepared in the examples and comparative examples was characterized using a Tesken MIRA3 field emission scanning electron microscope. Before testing, the lithium iron phosphate materials were dried and directly dispersed on conductive adhesive without additional coating treatment, then fixed on the sample stage for observation. Surface morphology images were acquired using a secondary electron detector, with an accelerating voltage set to a low voltage of 3-5 kV and a working distance set to 8-10 mm. The results are as follows: Figure 9 and Figure 10 As shown.
[0216] Figure 9 This is a SEM image of the lithium iron phosphate material prepared in Example 1. Figure 10 This is a SEM image of the lithium iron phosphate material prepared in Comparative Example 1. Figure 9 and Figure 10 The comparison shows that the lithium iron phosphate material prepared in the comparative example has more uncoated carbon sources, which are distributed in a mesh-like pattern on the surface of the lithium iron phosphate material, indicating poor coating ability; conversely, the lithium iron phosphate material prepared in the example has fewer uncoated carbon sources in a mesh-like pattern on the surface, indicating more uniform coating.
[0217] 4. The conductivity of the lithium manganese iron phosphate materials prepared in the examples and comparative examples was tested using the Xiamen Yuaneng four-probe powder resistivity PRCD2110.
[0218] The test results are shown in Table 2.
[0219] Example 3
[0220] 1. Batteries prepared using lithium iron phosphate as the positive electrode active material
[0221] The lithium iron phosphate material (LiFePO4) obtained in the above examples and comparative examples was mixed with the above raw materials in a mass ratio of LiFePO4:conductive carbon black:polyvinylidene fluoride (PVDF) = 8:1:1. N-methylpyrrolidone was added to prepare a positive electrode slurry with a solid content of 55%. This slurry was uniformly coated onto carbon-coated aluminum foil, vacuum dried, rolled, and punched into a 2.01 cm² area. 2 Electrode assembly. The negative electrode uses a lithium metal sheet, the separator uses Celgard 2400PE film, and the electrolyte uses a commercially available product (SS-SHRG004, Dongguan Shanshan Battery Materials Co., Ltd.). The positive electrode, separator, and negative electrode are assembled in one go in a glove box (high-purity Ar atmosphere), and then the electrolyte (1 mol / L NaClO4 + EC:DMC:EMC(1:1:1) +5% FEC) is injected to obtain a coin cell.
[0222] The coin cell was subjected to constant current charge-discharge cycle test at 25℃ and 0.1C, with a charge-discharge voltage of 2.0-3.7V. The initial coulombic efficiency was calculated. There was no special test method. The initial coulombic efficiency = initial discharge specific capacity / initial charge specific capacity. The coin cell batteries were tested for rate capability at 25°C and 2C. The test results are shown in Tables 1 and 2.
[0223] As can be seen from the test results in Table 1, compared with lithium iron phosphate materials prepared using conventional carbon sources, lithium iron phosphate materials prepared using the polymers of Examples 1-11 as carbon sources have significantly lower powder resistivity and increased compaction density under the same residual carbon content. The first discharge capacity, first coulombic efficiency and 2C rate performance of the prepared batteries are significantly improved, indicating that lithium iron phosphate materials prepared using the polymers of Examples 1-4 as carbon sources have excellent coin cell performance.
[0224] Comparing Comparative Examples 1-2 and Example 1, it is evident that, with the same total amount of carbon source, the lithium iron phosphate cathode material prepared using the polymer of this application as the carbon source has a significant advantage over the lithium iron phosphate cathode material prepared using PEG-based carbon sources. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared lithium iron phosphate cathode material. The polymer molecular structure of Example 1 incorporates polyether segments, aromatic rings, and nitrile groups. The introduction of polyether segments increases the polymer's solubility in water, making it suitable for preparing aqueous or alcohol-based cathode materials, thus compensating for the mismatch between benzene rings, nitrile groups, and solvents (water or alcohol). The introduction of aromatic rings increases the carbon content on the surface of the lithium iron phosphate cathode material, reducing the amount of carbon source added and the raw material cost of the cathode material. Furthermore, as a rigid structure, the aromatic ring more easily forms ordered graphitized coated carbon on the lithium iron phosphate surface. The introduction of nitrile groups promotes the formation of cyclic structures during the carbon source's pyrolysis process, thereby generating ordered coated carbon on the lithium iron phosphate surface.
[0225] Comparing Comparative Examples 3-5 with Example 1 illustrates the necessity of unsaturated polyether monomers, unsaturated aromatic monomers, and unsaturated nitrile monomers. When any one of these monomers is missing, the resistivity of the lithium iron phosphate powder material prepared from the polymer increases significantly, and the initial discharge capacity, initial coulombic efficiency, and 2C rate performance of the resulting battery all decrease significantly.
[0226] Comparing Examples 1 and 5-10, it is shown that changing the types of unsaturated polyether monomers, unsaturated aromatic monomers, unsaturated nitrile monomers, and acrylic compounds, as well as the amount of these four monomers, has little impact on the coin cell performance of lithium iron phosphate materials prepared using this polymer as a carbon source during the polymer synthesis process.
[0227] Comparing Example 1 and Example 11 demonstrates that glucose and polymer, as a combined carbon source, exhibit a stronger synergistic effect compared to the combined carbon source of PEG and polymer.
[0228] Table 1
[0229] 2. Batteries prepared using lithium manganese iron phosphate as the positive electrode active material
[0230] 85g of lithium manganese iron phosphate material, 5g of polyvinylidene fluoride, 10g of conductive carbon black, and 150mL of N-methylpyrrolidone prepared in the above examples and comparative examples were placed in a beaker and mechanically stirred at 500r / min for 4h to form a slurry. The slurry was coated onto aluminum foil with a single-sided thickness of 80μm using a doctor blade coater. The foil was first pre-dried in a 60℃ forced-air drying oven for 30min, and then transferred to a 120℃ vacuum drying oven for 12h. The dried electrode was compacted using a roller press with a pressure controlled at 110MPa and cut into electrode sheets with a diameter of 14mm to obtain the positive electrode. Using lithium foil as the negative electrode and a Celgard 2400 polypropylene microporous membrane as the separator, and 1 mol / L LiPF6 (EC:DEC = 1:1, v / v) as the electrolyte, the positive electrode, negative electrode, separator, and electrolyte were assembled in an argon glove box with water and oxygen content all below 1 ppm. After assembly, the cells were allowed to stand for 24 hours to obtain coin cells. The discharge specific capacity at 0.1C and 5C rates was tested under charge / discharge cutoff voltages of 3.0-4.3V; the capacity retention rate after 100 cycles at 5C charge / discharge rate was also tested. The results are shown in Table 2.
[0231] Table 2
[0232] As can be seen from the test results in Table 2, compared with lithium iron phosphate materials prepared using conventional carbon sources, lithium iron phosphate materials prepared using the polymers of Examples 12-15 as carbon sources have significantly improved conductivity. The 0.1C discharge specific capacity, 5C discharge specific capacity, and 5C capacity retention of the prepared batteries are all significantly improved, indicating that lithium iron phosphate materials prepared using the polymers of Examples 1-4 as carbon sources have excellent coin cell performance.
[0233] Comparing Comparative Examples 7-8 and Example 12, it is evident that, with the same total amount of carbon source, the lithium manganese iron phosphate cathode material prepared using the polymer of this application as the carbon source has a significant advantage over the lithium manganese iron phosphate cathode material prepared using PEG-based carbon sources. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared lithium manganese iron phosphate cathode material. The polymer molecular structure of Example 12 incorporates polyether segments, aromatic rings, and nitrile groups. The introduction of polyether segments improves the polymer's solubility in water, making it suitable for preparing aqueous or alcohol-based cathode materials and compensating for the mismatch between benzene rings, nitrile groups, and solvents (water or alcohol). The introduction of aromatic rings can increase the carbon content on the surface of lithium manganese iron phosphate cathode materials, reduce the amount of carbon source added and the raw material cost of cathode materials, and the aromatic rings, as rigid structures, are more likely to generate ordered graphitized coated carbon on the surface of lithium manganese iron phosphate. The introduction of nitrile groups promotes the formation of cyclic structures during the cracking process of carbon sources, thereby generating ordered coated carbon on the surface of lithium manganese iron phosphate.
[0234] Comparing Comparative Examples 8-10 and Example 12 illustrates the necessity of unsaturated polyether monomers, unsaturated aromatic monomers, and unsaturated nitrile monomers. When any one of these monomers is missing, the conductivity of the lithium iron phosphate material made from the polymer decreases significantly, and the 0.1C discharge specific capacity, 5C discharge specific capacity, and 5C capacity retention of the resulting battery all decrease significantly.
[0235] 3. Batteries prepared using sodium iron manganese phosphate (sodium iron manganese phosphate) as the positive electrode active material for sodium-ion batteries.
[0236] The sodium-ion batteries prepared in the above examples and comparative examples were uniformly mixed with sodium iron manganese phosphate positive electrode material, acetylene black, and PVDF binder, and then coated onto aluminum foil. After vacuum baking at 100°C for 4 hours, electrode sheets were obtained. Based on the total weight of the positive electrode material, acetylene black, and PVDF binder, the amount of positive electrode material was 80 wt%, the amount of acetylene black was 10 wt%, and the amount of PVDF binder was 10 wt%. Using the sodium sheet as the negative electrode, a glass fiber optic GF / A Whatman potassium sodium lithium battery filter membrane was used as the separator, and a 0.8 M NaPF6 / EC-DMC electrolyte was used. Button batteries were assembled and their charge-discharge characteristics were tested. The charge-discharge current was 0.1C, where 1C = 129 mA / g. The discharge specific capacity and average discharge voltage of the comparative and examples are shown in Table 3.
[0237] Table 3
[0238] As can be seen from the test results in Table 3, compared with sodium iron manganese phosphate material prepared using conventional carbon sources, the specific capacity and 100-cycle capacity retention of the battery prepared using the polymers of Examples 16-19 as carbon sources are significantly improved, indicating that the sodium iron manganese phosphate material prepared using the polymers of Examples 1-4 as carbon sources has excellent coin cell performance.
[0239] Comparing Comparative Examples 11-12 and Example 16, it is evident that, with the same total amount of carbon source, the sodium iron manganese phosphate cathode material prepared using the polymer of this application as the carbon source has a significant advantage over the sodium iron manganese phosphate cathode material prepared using PEG-based carbon sources. This demonstrates that the molecular structure of the carbon source has a substantial impact on the electrical performance of the battery assembled from the prepared sodium iron manganese phosphate cathode material. The polymer molecular structure of Example 16 incorporates polyether segments, aromatic rings, and nitrile groups. The introduction of polyether segments improves the polymer's solubility in water, making it suitable for preparing aqueous or alcohol-based cathode materials and compensating for the mismatch between benzene rings, nitrile groups, and solvents (water or alcohol). The introduction of aromatic rings can increase the carbon content on the surface of sodium iron manganese phosphate cathode materials, reduce the amount of carbon source added and the raw material cost of cathode materials, and the aromatic rings, as rigid structures, are more likely to generate ordered graphitized coated carbon on the surface of sodium iron manganese phosphate. The introduction of nitrile groups promotes the formation of cyclic structures during the cracking process of carbon sources, thereby generating ordered coated carbon on the surface of sodium iron manganese phosphate.
[0240] Comparing Comparative Examples 13-15 and Example 16 illustrates the necessity of unsaturated polyether monomers, unsaturated aromatic monomers, and unsaturated nitrile monomers. When any one of these monomers is missing, the specific capacity and 100-cycle capacity retention of the battery made from the polymer-derived sodium iron manganese phosphate material both show a significant decrease.
[0241] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.
Claims
1. A raw material composition for a positive electrode material, characterized in that, It includes a carbon source, which includes a polymer; The method for preparing the polymer includes the following steps: in the presence of an initiator, a base liquid, solution A and solution B are subjected to a polymerization reaction; The underlying solution comprises an unsaturated polyether monomer solution; solution A comprises a mixed solution of unsaturated aromatic monomers, unsaturated nitrile monomers, and acrylic compounds; solution B comprises a mixed solution of chain transfer agents and reducing agents. The unsaturated polyether monomer is an unsaturated polyoxyethylene ether; the unsaturated aromatic monomer is an unsaturated vinyl aromatic monomer; the unsaturated nitrile monomer is one or more of acrylonitrile, methacrylonitrile, and vinyl acetonitrile; the acrylic compound is one or more of acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, methyl methacrylate, butyl methacrylate, and hydroxyethyl methacrylate. The molar ratio of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer, and acrylic compound is 1.0:(0.2-7.0):(0.2-7.0):(0.2-8.0). The polymerization reaction is carried out at a temperature of 30-50℃ and for a time of 60-120 minutes.
2. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The polymerization reaction is followed by a purification step; the purification operation is vacuuming; during the purification, the vacuum degree of the system is -100 to -90 kPa.
3. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the cathode material satisfies one or more of the following conditions: (1) The unsaturated polyether monomer is an unsaturated alkenyl polyoxyethylene ether; (2) The unsaturated aromatic monomer is one or more of styrene, α-methylstyrene, vinyltoluene, and naphthalene; (3) The initiator is one or more of hydrogen peroxide, ammonium persulfate and cumene hydrogen peroxide; (4) The amount of the initiator is 0.2%-2% of the total mass of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer and acrylic compound; (5) The reducing agent is vitamin C and / or vitamin E; (6) The molar ratio of the initiator to the reducing agent is (2-7):1; (7) The chain transfer agent is one or more of mercaptoethanol, mercaptoacetic acid, mercaptopropionic acid, n-dodecyl mercaptoethanol, tert-dodecyl mercaptoethanol and octyl mercaptoethanol; (8) The amount of the chain transfer agent is 0.1%-3% of the total mass of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer and acrylic compound; (9) The solvents in the base liquid, solution A, and solution B are all ethyl acetate; (10) The total amount of solvent used in solution A and solution B is 0.2 to 4.0 times the total mass of the unsaturated polyether monomer, unsaturated aromatic monomer, unsaturated nitrile monomer and acrylic compound.
4. The raw material composition for the positive electrode material as described in claim 1, characterized in that, The raw material composition of the cathode material satisfies one or more of the following conditions: (1) The mass percentage of the carbon source in the raw material composition of the cathode material, excluding the solvent, is 2%-20%; (2) The polymer accounts for 20%-80% of the mass of the carbon source; (3) The carbon source also includes one or more of sucrose, glucose, polyethylene glycol, starch, citric acid and asphalt; (4) The carbon source is a polymer and glucose; the mass ratio of glucose to polymer is (0.2-2):1; (5) The carbon source is a polymer and polyethylene glycol; the mass ratio of glucose to polyethylene glycol is (0.2-2):1; (6) The positive electrode material is lithium iron phosphate, lithium manganese iron phosphate or sodium iron manganese phosphate.
5. A method for preparing a positive electrode material, characterized in that, It includes the following steps: sintering the precursor slurry to obtain the cathode material; the precursor slurry includes the raw material composition of the cathode material as described in any one of claims 1-4.
6. A positive electrode material, characterized in that, It is prepared using the method for preparing the positive electrode material as described in claim 5.
7. An electrode sheet, characterized in that, It includes the cathode material as described in claim 6.
8. A battery, characterized in that, It includes the electrode as described in claim 7.
Citation Information
Patent Citations
Special styrene-acrylate latex for wallpaper as well as preparation method and application thereof
CN106977661A